Controllable morphology of electrospun nanofiber membranes with tunable groove structure and the enhanced filtration performance for ultrafine particulates. (12th May 2021) - Lou, Yaoyuan; Ding, Shanshan; Wang, Bin; Wang, Jie; Sun, Qing; Jin, Xu; Li, Xiuyan
Abstract: As researchers are striving to develop high-performance filtration membranes with hierarchical micro/nano structures, the challenges and costs of processing often limit creative innovation. Here, we propose a polyethersulfone/polyacrylonitrile (PES/PAN) nanofiber membrane with groove structure by electrospinning and facile post-processing. The resulted membrane can form a groove structure on the surface of the fiber after being soaked in chloroform, thereby increasing the collision probability and extending the residence time for ultrafine particulates and improving the filtration efficiency. The groove structure can be attributed to the solubility of PES constituent in chloroform, while PAN constituent will not be dissolved, thus forming a high-performance nanofiber membrane with high filtration efficiency (ca. 99.54%) and withstand pressure drop (ca. 133.9 Pa) for dioctyl phthalate aerosol particles with diameter of 0.3 μ m. The results show that this convenient and low-cost fabrication technology can be used to prepare high-performance nanofiber membrane based air filters that have broad application prospects in respiratory protective equipment.